Political Linkages of the Indonesian Islamic Student Movement - Atmojo, Danang (Talenta Publisher, 2025)
This research discusses the political linkages built by Islamic student movement organizations, particularly in the case of Pergerakan Mahasiswa Islam Indonesia (PMII) Al-Ghozali Semarang. The research focuses on how such political linkages are built and operated by PMII Al-Ghozali Semarang with various institutional units in three domains: political society, civil society, and economic society. The findings in this study are that the political linkages built by PMII Al-Ghozali Semarang with political society tend to be stronger when approaching the election period, both in 2019 and 2024 due to pragmatic interests. Political linkages with civil society (especially those engaged in the religious field of Nahldatul Ulama) are very strong because of the similarity of values and ideology. Meanwhile, political linkages with the economic society are the weakest due to the small number of alumni engaged in the economic sector.